ANALISIS PENGARUH PENGETAHUAN, TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP IMBAL HASIL SAHAM SYARIAH DALAM PERSPEKTIP ISLAM DENGAN PENDEKATAN CIRCULAR CAUSATION DI BURSA EFEK INDONESIA - Hotman Tohir Pohan (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2014)
This research aims to identifr and analyze the influence of knowledge, social responsibility towards sharia stock returns in Bursa Efek Indonesia, with the approach of circular causation, further research in the underlying by differences between conventional and Islamic corporate social responsibility, where circular causation is the approach taken by the interaction between Variabels, namely between knowledge, capital structure, and returns islamic stocks. Results of this research are Islamic stocks negatively affected by corporate social responsibility, and positively influenced by knowledge, while knowledge positively influence corporate social responsibility that serves as an intervening, there is a reciprocal relationship between corporate social responsibility with return of Islamic stocks are corporate social responsibility a negative impact on stock returns syariah, and vice versa sharia stock returns negatively impact on corporate social responsibility, corporate social responsibility does not have a significant influence on stock returns sharia.